High Q factor modes in semiconductor nanoantennas for active nanophotonics and lasing - Mylnikov, Vasilii (Nanyang Technological University, 2021)
On-chip light sources are critical for the realization of fully integrated photonic circuitry. So far, semiconductor miniaturized lasers have been mainly limited to sizes on the order of a few microns. Further reduction of sizes is challenging fundamentally due to the associated radiative losses. While using plasmonic metals helps to reduce radiative losses and sizes, they also introduce Ohmic losses hindering real improvements. Here, we circumvent these fundamental issues using quasi-bound states in the continuum or supercavity modes and realize one of the smallest purely semiconductor nanolasers thus far. Coupling between a nanoparticle and a waveguide is studied as an extension of the original work. Multiple-particle 1D configurations, operating in lower azimuthal order modes, are optimized numerically and studied experimentally. The obtained results open a way for the realization of smaller low-loss dielectric nanolasers that might find applications in future photonic circuitry, among others.